Computational creativity: an analysis of M. Boden and G. Wiggins' theories (Technological Innovations Journal, 2023)
Computational creativity is a multidisciplinary intersection within the field of Artificial Intelligence, which has different objectives such as the development and evaluation of artificial systems capable of exhibiting creative behaviors. In this context, the works of Margaret Boden along with the subsequent problematization proposed by G.A. Wiggins can be considered as seminal conceptual references, which have allowed for various reflections and concrete theoretical foundations related to the subject matter. The works of both authors have been developed through diverse and distinct asynchronous publications, and in this sense, this paper condenses the different conceptual elements on types of creativity, conceptual space, and transformative and exploratory creative systems proposed throughout those works into a single theoretical-analytical framework. These elements are presented as a useful and efficient tool to establish formal theoretical criteria for evaluating capacities and abilities associated with creative behavior exhibited by artificial systems, both in current development and in speculative formulation for the future. Therefore, this article presents a comprehensive, detailed, and condensed analysis of Boden's work and Wiggins' subsequent problematization regarding key ideas, theoretical formulations, and concepts in the field of Computational creativity. In this regard, the present article contributes to the understanding and dissemination of the fundamental ideas in the field of Computational Creativity, establishing a condensed and detailed analysis of these topics, and serving as a reference for academic consultation.
Keywords: computational Creativity; machine creativity theory; AGI; philosophy of AI